Paraventricular Nucleus Infusion of Oligomeric Proantho Cyanidins Improves Renovascular Hypertension - Yu, Xiao-Jing; Xin, Guo-Rui; Liu, Kai-Li; Liu, Xiao-Jing; Fu, Li-Yan; Qi, Jie; Kang, Kai B.; Meng, Ting-Ting; Yi, Qiu-Yue; Li, Ying; Sun, Yao-Jun; Kang, Yu-Ming (Frontiers in Neuroscience, 2021)
Oxidative stress plays an important role in the pathogenesis of hypertension. Oligomeric proantho cyanidins (OPC) is the main polyphenol presents in grape seed and is known for its potent antioxidant and anti-inflammatory properties. In the present study, we hypothesize that OPC can attenuate oxidative stress in the paraventricular nucleus of hypothalamus (PVN), ameliorate neurotransmitter imbalance, decrease the blood pressure and sympathetic activity in renovascular hypertensive rats. After induction of renovascular hypertension by the two-kidney one-clip (2K-1C) method, male Sprague-Dawley rats received bilateral PVN infusion of OPC (20 µg/h) or vehicle via osmotic minipump for 4 weeks. We found that hypertension induced by 2K-1C was associated with the production of reactive oxygen species in the PVN. Infusion of OPC in the PVN significantly reduced the systolic blood pressure and level of norepinephrine in plasma of 2K-1C rats. In addition, PVN infusion of OPC decreased the level of ROS and the expression of stress-related NAD(P)H oxidase subunit NOX-4, increased the activity of Nrf2 and antioxidant enzyme (SOD-1), balanced the content of cytokines (IL-1β, IL-10) in the PVN, increased expression of inhibitory neurotransmitter (GAD67) and decreased the expression of excitatory neurotransmitter (TH) in the PVN of 2K-1C rats. Our findings provide strong evidence that PVN infusion of OPC inhibited the progression of renovascular hypertension through its potent anti-oxidative and anti-inflammatory function in the PVN.